The Impact of Ambassador Animal Facilitated Programs on Visitor Curiosity and Connections: A Mixed-Methods Study - Shelley J. Rank (Animal Behavior and Cognition, 2021)
Many zoos and aquariums offer opportunities for visitors to have up-close encounters with ambassador animals; however, the impacts of these experiences on visitors’ connections to animals are not well documented. We used observations and family interviews in a sequential mixed-methods research study to explore how animal ambassador programs impact participants. We found that the type of ambassador animal did not affect the number of questions or comments made by participants during programs, suggesting broad interest in animals. Programs in which facilitators prompted participants with questions were especially successful at eliciting questions and guiding the topics of those questions, fueling deeper curiosity. Interviewees described themselves as “animal people” and self-reported practicing conservation behaviors, suggesting that their animal affiliative and pro-environmental identities could be leveraged to discuss conservation issues and encourage solutions-based behaviors. Lastly, opportunities to meet ambassador animals increased participants’ feelings of connecting to animals, building on previous research and corroborating findings. Programs should consider how to further build on these positive learning and affective outcomes by capitalizing on opportunities to provide deep insights into conservation issues and actions related to the ambassador animals.